Basic structure of a regulation for Game of Hands: an alternative combat method - Abadía Córdoba, Walner Yon
This paper is the result of a research project focusing on structuring a regulation for the combat method named “Game of Hands”, from the technical characteristics of its different modalities. A descriptive study with a propositional scope was developed, through a case study design that used the inductive method. The information was obtained by documentary consultation, audiovisual exploration, dialogue with experts and direct observation of empirical players. The scope of the objectives allowed the definition of three competition modes: open combat with the relay sub mode, close combat and close combat with a stick. All of them coincide in defense technique (high, medium and low), although close combat with a stick differs in guard and attack and also does not use protective implements for the hands. Likewise, the characteristics ofthe scenario were established: measurements and delimitation by colors and some basic scoring rules. It is concluded that the requirements of each modality demarcate the technical gestures and the competition rules for Game of Hands.